Oil and Gas Wells - Ouadfeul, Sid-Ali; Aliouane, Leila (IntechOpen, 2020)
The aim of this book is to present some advances in different aspects of oil and gas technology. Two chapters are dedicated to the scientific research in the domain of reservoir engineering and characterization. Four chapters are dedicated to the field of well drilling and performance and another chapter is related to oil and transport.